Physiological functions of oral cavity - Herud, Anna; Śmiech-Słomkowska, Grażyna (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
Oral cavity is the organ where all functions important for the body take place. Oral cavity is responsible for breathing, speech and food intake, which depending on stage of development, is suckling or mastication. The improvement of these functions comes with neuromuscular development of muscles building and surrounding oral cavity and with gradual development of dentition. There are structures mutually dependent and these are lips, cheeks, tongue, floor of the mouth, palate, pharynx, masticatory muscles, facial muscles and inner and outer tongue muscles. All listed structures play role in physiological functions of oral cavity, and oral cavity dysfunction affects the changes in the stomatognatic organ.